Nunavut - Parker, O.C., John H. (ARCTIC, 1999)
On April first, Nunavut became a reality - the first change in Canada's geopolitical boundaries since the 1949 addition of Newfoundland and Labrador. . There is recognition in Nunavut that the road ahead will be difficult. But there is an enthusiasm for the task, rather like the enthusiasm that prevailed in 1967 when the Territorial administration moved north out of Ottawa and the Territorial Council began its rapid growth to fully elected status. In the ensuing years, the Inuit embraced elected government and, through education and experience, readied themselves for Nunavut. They are fortunate indeed in having a core of long-time public servants, dedicated to the east, to work with them in the months to come. The challenges faced by the people of Nunavut are considerable. The solutions they seek will be of their own making, and therein lies their strength. .